Budaya Religius Sebagai Hidden Kurikulum Dalam Membentuk Karakter Islami di Madrasah Ibtidaiyah Miftahul Huda Gebangsari - 'Ulyan, Mohammad; Achmad, Syaefudin (Universitas Wahid Hasyim Semarang, 2023)
The flow of globalization which has had an influence in various fields has brought about major changes in the world order. This research will discuss Religious Culture as a Hidden Curriculum in Shaping Students' Islamic Character at Madrasah. This research was conducted in an effort to maintain Islamic character values through religious culture which is included in the hidden curriculum. The type of research used is qualitative research, which is a research process that produces descriptive data in the form of written and spoken words from the people and actors being observed. This research is also included in the type of field research, namely research by going directly to the research location. The results of the research show that the hidden implementation at madrasah takes the form of memorizing juz 'amma, dhuha prayers in congregation, monthly donations, getting used to praying in congregation. The learning methods used in forming Islamic character use the method of saving verses, dhuha prayers, dhuhur prayers in congregation, kultum, and shaking hands when going to and from school.